2002
DOI: 10.1152/jn.2002.88.4.1968
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Magnitude of Movement-Related Gating of Tactile Detection in Humans. III. Effect of Motor Tasks

Abstract: This study investigated the relative importance of central and peripheral signals for movement-related gating by comparing the time course and magnitude of movement-related decreases in tactile detection during a reference motor task, active isotonic digit 2 (D2) abduction, with that seen during three test tasks: a comparison with active isometric D2 abduction (movement vs. no movement) evaluated the contribution of peripheral reafference generated by the movement to gating; a comparison with passive D2 abduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 70 publications
(86 reference statements)
6
84
2
Order By: Relevance
“…Tactile detection was less accurate during both movement conditions (back, arm) than in the no movement condition, further adding to the evidence in support of the phenomenon of tactile suppression (Chapman and Beauchamp, 2006;, Juravle et al, 2010, Post et al, 1994, Voss et al, 2008, Wasaka et al, 2003, Williams and Chapman, 2000, Williams and Chapman, 2002and Williams et al, 1998. The results also revealed that the phenomenon of tactile suppression is not limited to movements of the limbs (most studies used movements of the arms, hands, or fingers), but also emerges during back movements, replicating a previous study (Van Hulle et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Tactile detection was less accurate during both movement conditions (back, arm) than in the no movement condition, further adding to the evidence in support of the phenomenon of tactile suppression (Chapman and Beauchamp, 2006;, Juravle et al, 2010, Post et al, 1994, Voss et al, 2008, Wasaka et al, 2003, Williams and Chapman, 2000, Williams and Chapman, 2002and Williams et al, 1998. The results also revealed that the phenomenon of tactile suppression is not limited to movements of the limbs (most studies used movements of the arms, hands, or fingers), but also emerges during back movements, replicating a previous study (Van Hulle et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…As an example of such a filtering mechanism just take the phenomenon of tactile suppression, which refers to the intriguing observation that voluntary movement results in reduced levels of somatosensation (Chapman andBeauchamp, 2006 andVitello et al, 2010). Tactile suppression has been well documented in studies showing that the execution of a movement attenuates the detection of light, near-threshold tactile stimuli, particularly when delivered to the moving body part (Chapman and Beauchamp, 2006, Juravle et al, 2010, Post et al, 1994, Voss et al, 2008, Wasaka et al, 2003, Williams and Chapman, 2000, Williams and Chapman, 2002and Williams et al, 1998. Whereas tactile suppression has typically been demonstrated for those movements involving the fingers or the hands, a recent study also showed that back movements result in an attenuation of the detection of tactile stimuli administered to the back (Van Hulle et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…‱ Tactile afference suppression: Prior research has indicated that tactile sensations in the hand are suppressed during some movement tasks (e.g., [8,11]). However, the demonstrated suppression effects involve weak stimuli near sensory thresholds, thus do not seem significant enough to explain the results reported here, which involve signals that are far above previously reported force detection thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…But while it is consistent with the temporal compression hypothesis, this result could also have occurred because impaired discrimination occurred for reasons that had nothing to do with time. There may instead have been sensory overload or numbing of the finger, insofar as the shocks were delivered on the finger that was both the source of the action and the locus of the temporal discrimination (e.g., Williams & Chapman, 2002). Although these perceptual effects suggest that time compression might occur as a result of voluntary action, the inference would be more convincing if a phenomenal or perceptual change were to be manifested in a sensory modality and bodily location that were removed from the action itself.…”
mentioning
confidence: 99%